KEDUDUKAN ANAK ANGKAT DALAM PEMBAGIAN WARISAN MENURUT HUKUM ADAT BATAK TOBA - Satria Braja Hariandja (Universitas Islam Sumatera Utara, 2019)
The result of this research shows that the position of adopted children in the inheritance distribution of the traditional law of Batak Toba is still different from that of biological children so that in terms of mastery and ownership the distribution causes injustice. However, the rights of adopted children in the Toba Batak tradition can be equated with those of biological children. It is because before a child is adopted or appointed, the child must pass a certain customary process to prove that he has been legally customary to become a clan of his adoptive parents. There is a shift in traditional values, and this is because there is no rule of adoption of children and its legal consequence.Those who have been adopted will be accepted as biological children and kinship arises between children and relatives in the dalihan na tolu environment. The research method used in this study is normative research by applying a statue approach and conceptual approach. Keywords: Adopted Child, Heritage, Batak Toba